IMPLEMENTATION OF THE RANK ORDER CENTROID (ROC) METHOD TO DETERMINE THE FAVORITE BETTA FISH - Saut Parsaoran Tamba; Alvin Purba; Yogga Eka Kusuma; Mang Ayu Santi Vidyastuti; Surya Dharma (INFOKUM, 2021)
Betta fish is one of the most popular fish in Indonesia. Apart from being a beauty, this fish is also often made into a match with one betta fish with another. Fish that are beautiful and can fight have a high selling price to the public. Therefore, it is necessary to make a study that aims to choose a good betta fish so that it becomes a favorite and will become a betta fish with a high selling price. The criteria examined were the color of the fish, the shape of the fins, the shape of the tail, the tie of the fish, the body, the head and the mentality of the fish. The results obtained are betta fish that have an albino color shape, brave and calm mentality, good fin shape, very good tail shape, fish tie with a balanced length, proportional and smooth fish body even though it has a fish head in poor condition (bad). ). It can be concluded that the most important criteria to be assessed are fish color, fish mentality, fin shape, tail shape, fish tie and fish body. The method used in this study is rank order centroid (ROC).